Pendidikan keluarga Islam menurut pemikiran Abdullah Nashih Ulwan - Imas Sukma Nur Saida; Hafidz Hafidz; Intan Nur Amalia (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to find out the concept of Islamic family education, the study of the thoughts of a reformer who has the role of creative and progressive thinking, namely Abdullah Nashih Ulwan. Islamic family education is needed in the stage of child development. The family is the first madrasa that the child will imitate and will affect the child's future. If in the family is not taught religion and civilization and good and true morality in accordance with Islamic teachings, it will affect the morals and morals of children in the future. This research is a literature type research using a qualitative descriptive approach. The source of data in this study is a reformer of Islamic family education, namely Abdullah Nashih Ulwan. Data analysis techniques in this study are data reduction, data presentation, and conclusions. Data collection in this study is by documentation from Abdullah Nashih Ulwan's shop thought study. The results of this study show that Abdullah Nashih Ulwan's thoughts, a reformer, about Islamic family thought are very influential on akhlaq and creed in one family, one of which is on child development, very influential in family education, if wrong in educating children, it is also wrong for them to take good care of children for life. The supporting factor for the success of mothers and fathers in the process of forming Islamic family is to make children who are strong in good civilized research, have noble morals and become human beings who are beneficial to the country and also the Islamic religion.